Hubungan Pola Asuh Orang Tua dalam Menstimulasi Perkembangan Motorik Kasar dan Halus Usia Pra Sekolah - MUNIR, ZAINAL; Yulisyowati, Yulisyowati; Virana, Helpy (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
At this stage of growth and development of children pre- school age 3-4 years, children begin to master a variety of physical skills and courage. However, there are still come pre school age children are to afraid of being in a foreign environment at school. If that happens then the pre school children have delays in development. Child development is influence by the pattern of care applied by the parents. Authoritative parenting strongly influence the high level of courage and skill of children. The study aims to determine the relationship of parenting the parent to stimulate the development of groos motor and fine motor skills in children. Research methods and correlational design using cross sectional approach by using purposive sampling techniqus sampling. The population of this study were parents with pre school age children 3-4 years in early childhood AL-Firdaus Bahrul ‘Ulum Tambakberas Jombang, which amount to 32 people with a large sample of 22 people. Method of data collection use questionnaires and observation sheets DDST (Denver Development Screening Test), and then data is analyzed by Chi-Square test. The result of correlation analysis Chi-Square majority of respondents found that authoritative parenting implement as many as 20 people (90,9%) with development of gross motor that delay. Respondent who apply the authoritative parenting style with development of fine motor skills that normal . And indulgent parenting style with development of fine motor skills that delay with Asymp. Sig ρ = 0.000, which means there is a relationship between the pattern of care in stimulating the development of gross motor and fine motor skills of children. From this research it can be concluded that authoritative parenting pattern can be applied to parents of pre school children aged 3-4 years so that children growth and develop well in early childhood Bahrul ‘Ulum AL-Firdaus Tambakberas Jombang.Keywords: Parenting pattern, gwoth and development, Denver Development Skrining Test